Controle de tensão em sistemas de distribuição considerando a inserção de veículos elétricos e qualificação apresentada ao programa de pós - Araújo, Iuri Santos de (2017)
The arrival of the electric vehicles to Brazil will imply a great impact on the consumption of electric energy and the energy concessionaires will have to adapt to this new scenario. In this work is considered a participation of electric vehicles using a distribution network to recharges through the concessionaire of electric energy distribution. Considering the behavior of ordinary users, the network voltage levels during vehicle loading are checked. Since a new power demand can compromise the voltage levels of the secondary grid, it is proposed a method of voltage control of the secondary grid considering the voltage prediction. A prediction has occurred through past voltage information, and the voltage control is performed to avoid exceeding permitted limits. The performance of the control can occur either through the switching the tap of electric distribution transformers or through the energy injection by the energy storage. The results prove that the prediction technique based on least squares methods is quite efficient and showed satisfactory results of the voltage control in the quasistatic regime.